2021
DOI: 10.1002/jcb.29883
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer cell‐derived EDA‐containing fibronectin induces an inflammatory response from monocytes and promotes metastatic tumor microenvironment

Abstract: Tumor-associated macrophages (TAMs) play a pivotal role in facilitating tumor growth and metastasis. This tumor-promoting propensity of TAMs sets in as a result of their complex cross-talk with tumor cells mediated primarily by tumor cell-secreted proteins in the tumor microenvironment. To explore such interactions, we employed an immunoscreening approach involving the immunization of Balb-c mice with model human lung carcinoma cell line, A549. From serological examination combined with mass spectrometric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…These findings indicate that the innate immune response to fibronectin-derived DAMPs is cell type-specific, both with respect to the DAMPs recognized and the amount of cytokine released. Previous studies in numerous model systems and cell types have consistently demonstrated that the activation of the innate immune response by the FnEDA domain is mediated through the TLR4-dependent activation of NFκB [24,[41][42][43][44][45][46][47][48][49]. However, after testing several neutralizing antibodies to various TLRs including TLR4 (data not shown), we found that in MDA-MB-468 cells, IL-8 release in response to FnEDA was entirely dependent on TLR5 (Figure 2A).…”
Section: Resultsmentioning
confidence: 65%
“…These findings indicate that the innate immune response to fibronectin-derived DAMPs is cell type-specific, both with respect to the DAMPs recognized and the amount of cytokine released. Previous studies in numerous model systems and cell types have consistently demonstrated that the activation of the innate immune response by the FnEDA domain is mediated through the TLR4-dependent activation of NFκB [24,[41][42][43][44][45][46][47][48][49]. However, after testing several neutralizing antibodies to various TLRs including TLR4 (data not shown), we found that in MDA-MB-468 cells, IL-8 release in response to FnEDA was entirely dependent on TLR5 (Figure 2A).…”
Section: Resultsmentioning
confidence: 65%
“…However, tumor immunosuppressive microenvironment including the recruitment of regulatory T cells and myeloid derived suppressor cells, as well as hypoxia, high interstitial fluid pressure, and physical barriers, make the immune response not efficient for therapeutic vaccinations for established tumor. EDA-E7 as a therapeutic vaccine has already been shown to eradicate large tumor in mice by repeated intratumor injection, which could possibly be because EDA could not just activate DCs through TLR4 signaling pathway, but also create a pro-inflammatory microenvironment in tumor as reported by other groups, and attract the infiltration of activated T cells [ 10 ]. In addition, in vitro generation of HPV vaccine is expensive and time consuming, as well as difficult to standardize each batch of product.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ex vivo DCs-based vaccine is difficult to standardize, therefore, in vivo induction of DCs with HPV antigen as vaccine for cervical cancer has great potential for clinical application. It was reported that the spliced exon encoding the type III repeat extra domain A (EDA) from fibronectin, which is produced in response to tissue injury and works as a damage-associated molecular pattern molecule [ 9 ], is able to target antigens to DCs while inducing maturation through TLR4 ligation [ 10 , 11 , 12 , 13 ]. Moreover, scientists have amplified mouse origin EDA and constructed recombinant fusion protein EDA-E7 (HPV16E7), then evaluated the immune response in mouse condition and found that EDA-E7 could efficiently induce specific immune rejection of HPV16E7 infected TC-1 tumors [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides acting as a building block of ECM, Fibronectin is well known to play a crucial role in cell–cell adhesion, cell migration, wound healing, host‐pathogen interactions and cancer (Baghban et al, 2020; Patten & Wang, 2021; Rick et al, 2019). The cell surface receptors through which Fibronectin exerts varied functions are integrins and the presence of EDA and EDB domains impart heterogeneity to Fibronectin function through their binding to different integrins (Amin et al, 2021). Arg‐Gly‐Asp (RGD) sequence located in the FNIII10 repeat mediates the interaction of Fibronectin to its primary receptor, α5β1 integrin (Main et al, 1992; Pytela et al, 1985; Roumen Pankov, 2002; Ruoslahti, 1984).…”
Section: Introductionmentioning
confidence: 99%